Satisfaction among the patients attending the health centres attached to a tertiary care hospital in Gandhinagar, Gujarat - Jadav, Pranay A. (International Journal Of Community Medicine And Public Health, 2018)
Background: There is a need of quality health services in developing countries like India. Uneducated patients are transformed in to educated clients and demands for better services. It is important to measure satisfaction of the patients towards catered health services for betterment of the institute as well as community. The objective of the study was to know the satisfaction of patients attending the OPD of Rural health training centre and urban health training centre of a medical college. Methods: A cross-sectional survey was conducted among people attending the OPD of RHTC and UHTC of a Medical college and they were interviewed by using patient satisfaction survey from. Results: Overall satisfaction was 98% participants in RHTC and 99% in UHTC were satisfied. Almost all patients were satisfied with the behaviour of the doctor, paramedical staff and class 3 workers at RHTC and UHTC (100% in RHTC and 98.5% in UHTC. Conclusions: Overall patient satisfaction was good but based on the statistics; areas which had a void can be corrected by implementing the suggestions given by respondents.